2021
DOI: 10.1021/acsomega.1c01521
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Electrochemical Properties of Ti-Doped LiMn2O4 Spinel Cathode Materials Using a One-Step Hydrothermal Method

Abstract: In this study, LiMn 2– x Ti x O 4 cathode materials were synthesized by a simple one-step hydrothermal method, and the effects of Ti doping on the sample structure and electrochemical properties were examined. The results indicated that Ti doping did not affect the spinel structure of LiMn 2 O 4 , and no other hybrid phases were produced. Furthermore, appropriate doping with Ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 55 publications
(69 reference statements)
1
18
0
Order By: Relevance
“…To explore the effect of Al and Ti codoping in the spinel structure, undoped, Al-doped, Ti-doped, and Al and Ti codoped LMO samples were evaluated in lithium-ion cells. It has been reported that Al-doping or Ti doping in LMO spinel is beneficial for overall cell performance while losing some capacity due to the electrochemical inactivity of Al and Ti dopants. , In both cases, however, the doping element helps to overcome the Mn dissolution problem during cycling by perturbing the long-range direct Mn–Mn interaction through the shared edges . Despite the previous studies on elemental substitution, the codoping of LMO spinel with a small amount of both Al and Ti has not yet been investigated systematically. , Accordingly, the electrochemical characteristics of the Al and Ti codoped LMO cathodes are compared with the singly doped and undoped LMO cathodes.…”
Section: Resultsmentioning
confidence: 99%
“…To explore the effect of Al and Ti codoping in the spinel structure, undoped, Al-doped, Ti-doped, and Al and Ti codoped LMO samples were evaluated in lithium-ion cells. It has been reported that Al-doping or Ti doping in LMO spinel is beneficial for overall cell performance while losing some capacity due to the electrochemical inactivity of Al and Ti dopants. , In both cases, however, the doping element helps to overcome the Mn dissolution problem during cycling by perturbing the long-range direct Mn–Mn interaction through the shared edges . Despite the previous studies on elemental substitution, the codoping of LMO spinel with a small amount of both Al and Ti has not yet been investigated systematically. , Accordingly, the electrochemical characteristics of the Al and Ti codoped LMO cathodes are compared with the singly doped and undoped LMO cathodes.…”
Section: Resultsmentioning
confidence: 99%
“…This phenomenon is ascribed to the low conductivity of LiMn 2 O 4 and the Jahn-Teller distortion arising from the thermodynamic instability of the spinel lattice. 9,45,46 In order to investigate the intercalation of Li + ions into Mo 6 S 8 nanocubes, ex situ post-mortem XRD and XPS measurements were performed on cycled electrodes. The full cell was charged and discharged at a 0.2 C rate and the negative electrode was recovered from the cell and washed thoroughly with water before the measurements.…”
Section: Resultsmentioning
confidence: 99%
“…This phenomenon is ascribed to the low conductivity of LiMn 2 O 4 and the Jahn–Teller distortion arising from the thermodynamic instability of the spinel lattice. 9,45,46…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the inclusion of suitable metal dopants were able to eliminate the impurity phases. Facile hydrothermal method suggested by Zhang et al achieved a highest initial discharge capacity (352.8 mAhg −1 ) with layered material and faded drastically after 50 cycles with a capacity retention of 75.5% 8‐11 …”
Section: Introductionmentioning
confidence: 99%